1998
DOI: 10.1063/1.477368
|View full text |Cite
|
Sign up to set email alerts
|

Responses of an immobilized-catalyst Belousov–Zabotinsky reaction system to electric fields

Abstract: Effect of an external electric field on the diffusion-influenced geminate reversible reaction of a neutral particle and a charged particle in three dimensions. III. Ground-state ABCD reaction

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 23 publications
(22 reference statements)
0
3
0
Order By: Relevance
“…Experiments were carried out with a localized reaction system in which the tris-(2,2Ј-bipyridine) ruthenium (II) complex ͓Ru͑bpy͒ 3 2+ ͔ was immobilized in cation exchange beads of submillimeter size [16,17]. The experimental setup is almost the same as those described in an earlier paper [14].…”
Section: Methodsmentioning
confidence: 99%
“…Experiments were carried out with a localized reaction system in which the tris-(2,2Ј-bipyridine) ruthenium (II) complex ͓Ru͑bpy͒ 3 2+ ͔ was immobilized in cation exchange beads of submillimeter size [16,17]. The experimental setup is almost the same as those described in an earlier paper [14].…”
Section: Methodsmentioning
confidence: 99%
“…Theoretical studies on the analysis of chemical wave propagation have suggested that an applied field may significantly alter wave propagation. , A DC electric field in the BZ reaction can alter the wave velocity, and it can also cause annihilation and splitting of the waves. , The spiral wave is forced to drift in the direction of the anode but with a perpendicular velocity component whose direction is determined by the chirality of the spiral. ,, The spiral can be dragged in this fashion and ultimately removed from the medium. An electric field can unpin a pinned spiral wave if the applied current is above a threshold current density .…”
Section: Introductionmentioning
confidence: 99%
“…According to the physical preconditions, excitable media are critically dependent in their behaviour on small external forces (Sagues and Epstein 2003;Tabony 2006), and accordingly wave propagation in BZ-systems has been studied depending on a variety of such forces, as there are for example small currents, electro-magnetic fields (Blank and Soo 2003;Miyakawa and Mizoguchi 1998;Sontag 2006) and others (Schmidt and Müller 1997;Ševčíková et al 1996).…”
Section: Introductionmentioning
confidence: 99%